A Forensic Approach in the Determination of Sequence of Strokes using Fluorescence Spectrometry - Vartika Khare; Anu Singla; Pawan Gupta (Journal of Forensic Science and Medicine)
Background: Fluorescence Microscope is a promising analytical method for the examination of the sequence of strokes of writing inks of different colours, brands, and models in a questioned document. Aims and Objectives: In the present article, an attempt has been made to categorize the writing inks of different brands and colours on the basis of their fluorescence. Materials and Methods: A total of 36 writing inks were used to make the different intersections on a standard A4 sheet which were then analyzed under the excitation filters of the Fluorescence Microscope. Results: The results indicated that the different inks can be characterized optically based on the luminescent components of the ink present in crossed lined intersections. Conclusions: Fluorescence Microscopy is a relatively simple, fast, inexpensive, and non-destructive technology that can be used in conjunction with other, more complex, and expensive technologies to identify the sequence of line crossing. It can provide a novel way of analysis based on the assessment of microelement analysis and the characteristics of diverse ink handwriting samples.